1999
DOI: 10.1046/j.1469-8137.1999.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses to flooding intensity in Leontodon taraxacoides

Abstract: Natural flooding is one of the major factors affecting vegetation dynamics in many regions of the world. The Flooding Pampa Grasslands (Argentina) are frequently exposed to flooding events of diverse intensity and duration, some of which Leontodon taraxacoides, an exotic dicot. frequent in these grasslands, seems to survive. Its responses to four different water depths (0, 1, 7 and 13 cm) were studied. The results indicate that plants in conditions of total submergence (depth of 13 cm) did not survive. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 32 publications
0
44
0
2
Order By: Relevance
“…Hyponastic growth in R. palustris occurs mainly in petioles of younger leaves, and results from differential cell elongation across the petiole base (Cox et al 2004). Hyponastic growth alone, is a trait of relevance as vertical re-orientation by itself can bring leaves above the water; an example is L. taraxacoides that does not display a shoot elongation response (Grimoldi et al 1999). Even if hyponastic growth occurs and leaves do not reach the water surface, potential benefits might still be improved access to light, shortening of the submergence period, and prevention of sediment/debris covering leaves.…”
Section: Shallow Submergence -Long Durationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyponastic growth in R. palustris occurs mainly in petioles of younger leaves, and results from differential cell elongation across the petiole base (Cox et al 2004). Hyponastic growth alone, is a trait of relevance as vertical re-orientation by itself can bring leaves above the water; an example is L. taraxacoides that does not display a shoot elongation response (Grimoldi et al 1999). Even if hyponastic growth occurs and leaves do not reach the water surface, potential benefits might still be improved access to light, shortening of the submergence period, and prevention of sediment/debris covering leaves.…”
Section: Shallow Submergence -Long Durationmentioning
confidence: 99%
“…(Grimoldi et al 1999), Paspalum dilatatum Poir. (Insausti et al 2001), and even Arabidopsis (Millenaar et al 2005).…”
Section: Shallow Submergence -Long Durationmentioning
confidence: 99%
See 1 more Smart Citation
“…These nastic responses (Palmer, 1985) can be divided into epinastic (downward) and hyponastic (upward) curvatures and are caused by differential growth, with, respectively, the adaxial (upper) or the abaxial (lower) side of the organ growing more rapidly (Kang, 1979). One of the environmental factors inducing hyponastic leaf movement is flooding (Ranunculus repens and Caltha palustris, Ridge, 1987; Leontodon taraxacoides, Grimoldi et al, 1999;Paspalum dilatatum, Insausti et al, 2001;Rumex palustris, Cox et al, 2003). In the semiaquatic species R. palustris, hyponastic growth upon complete submergence, together with stimulated petiole elongation, contributes to increased survival by enabling the leaves to reach the water surface so that gas exchange with the atmosphere is restored (for review, see Voesenek et al, 2003).…”
mentioning
confidence: 99%
“…Similarly, Rubio & Lavado (1999) Brachiaria spp. Also, a higher proportion of biomass allocated to leaves was observed in flooded Leontodon taraxacoides (Asteraceae) by Grimoldi et al (1999). In contrast, Mattos et al (2005) reported that flooding caused a lower LMR in Brachiaria spp.…”
Section: Resultsmentioning
confidence: 89%